Bordeaux : l'impossible fabrique d'un territoire viticole bio ? - Frédérique Célérier (EchoGéo)
This paper intends to study the development of organic wine production in the Bordeaux vineyard. The spread of organic wine-producing practices is stimulated by an increasing demand, and by a more and more organised sector. Organic wine actors have initiated an approach of territorial construction, that will guarantee the quality of wines only identified by their methods of production. The construction of an organic territorial identity is hindered by the strength of the territorial quality model in the Bordeaux vineyard context.